EVALUASI INPUT PEMBELAJARAN MEMBACA DI SEKOLAH DASAR - Arnumasari, Riyani Eka; Rahmawati, Laili Etika (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2022)
The low reading ability of students is a concern for the world of education which needs to find a comprehensive solution, one of which is to review from the input side in learning. This study aims to describe the evaluation of the learning inputs of reading in elementary schools. The research method used is an evaluation with a descriptive approach. The results showed that the background of learning to read was in accordance with the school's vision and mission, there was a discrepancy between the educational background of the teacher and the field of elementary school, inadequate infrastructure, less optimal use of the library, and the economic level of SD Luwang 01 that was categorized as lower middle class. It was yielded from the  questionnaires distributed to 58 respondents showing that the educational background of parents was elementary school graduates 14%, junior high graduates  24%, high school graduates 54%, and university graduates 8%. The working backgrounds of the students' parents include tailors 1%, civil servants 3%, entrepreneurs 3%, farmers 4%, traders 13%, not working 18%, casual daily labourers 21%, and private employees 37%.